2011
DOI: 10.1111/j.1939-165x.2011.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant and antioxidant profile of hyperketonemic ewes affected by pregnancy toxemia

Abstract: Oxidative stress and lipid peroxidation are involved in the development and complications of pregnancy toxemia. An association between hyperketonemia and the products of lipid peroxidation has also been demonstrated, suggesting that ketosis is a risk factor in the development of lipid peroxidation and oxidative stress in ewes affected by pregnancy toxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
3
23
0
2
Order By: Relevance
“…Particularly, gravidic toxaemia develops in the last 6 weeks of pregnancy, when foetuses reach two‐thirds of their prenatal development and seems to occur mostly in twin pregnancies with two or three foetuses (Al‐Qudah ).…”
Section: Ros and Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, gravidic toxaemia develops in the last 6 weeks of pregnancy, when foetuses reach two‐thirds of their prenatal development and seems to occur mostly in twin pregnancies with two or three foetuses (Al‐Qudah ).…”
Section: Ros and Pregnancymentioning
confidence: 99%
“…These ketone bodies, particularly acetoacetate, induce the generation of hydroxyde anion (HO‐), O2 · , which, in turn, will lead to hydroxyl radical (OH . ) formation (Lebovitz ; Al‐Qudah ). Once generated, ROS exert their cytotoxic effect inducing lipo‐peroxidation in cell membranes, with consequent formation and storage of the byproducts of such an oxidation, the so‐called ‘Thiobarbituric Acid Reactive Substances’, (TBARS) (Al‐Qudah ), which, upon binding to many constituents of the cell membrane, lead to an alteration in cell membrane permeability as well as in lipid organization and consequent morfo/functional cell damage (Gutteridge ).…”
Section: Ros and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, early observations of constriction of the aorta in pregnant rabbits revealed that such manipulation generated hypertension, proteinuria, weight gain, and reduced weight of the fetus 139 . Finally, sheep experience what is call toxemia of pregnancy, that appears to be a very different metabolic disorder as compared to preeclampsia 140 , but does include proteinuria and inflammation 141 .…”
Section: Preeclampsiamentioning
confidence: 99%
“…OPT causes significant economic losses to the sheep industry due to maternal and foetal death (Schlumbohm & Harmeyer, 2008;Jyothi et al, 2014;Tharwat & Al-Sobayil, 2014) and occurs with a greater incidence in animals carrying two or more foetuses; it can also be observed in poorly nourished sheep carrying a single foetus (Al-Qudah, 2011), when winters are rigorous and nutritional deficiencies occur (Sigurdsson, 1988;Cal-Pereyra et al, 2012). In most cases, this pathology is also accompanied with hepatic fatty infiltration (Van Saun, 2000).…”
Section: Introductionmentioning
confidence: 99%